Grachevskaya and Mechetnaya Fortresses of Tsaritsyn Guard Line at the 18th Century Plans and Aerial Photographs from 1942–1943 - Andrei Lapshin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2023)
Introduction. The aim of the work is to establish the degree of consistency and graphical reliability of the information in existing manuscript plans of fortresses of Grachevskaya and Mechetnaya of the Tsaritsyn guard line drawn in the 18th century in comparison with their ruined remains which were recorded in the middle of the 20th century. One of the main tasks is to present new sources for the study of Tsaritsyn guard line: photo materials of 1942–1943 and a topographical plan. They reliably allow us to recognize not only about the exact location and configuration of the Mechetnaya and Grachevskaya fortresses, but also about their basic dimensions. The relevance of the research topic is due to the fact that at present these sites no longer exist, and information about them has survived only in photographic or topographic form, which is introduced into scientific data for the first time. Methods and materials. The study is based on published material, archival manuscript plans from the 18th century, as well as aerial photographs from 1942–1943 and a topographical plan from the 1970s. Special technical methods of combining plans and maps with modern satellite imagery of terrain geo-information resources have allowed to compare these contemporaneous documents. Analysis. A comparative analysis of the size, shape and location of the fortresses of Grachevskaya and Mechetnaya, as well as some other sections of Tsaritsyn guard line, has been made. The article provides a comparative analysis of manuscript plans of 18th century fortresses, aerial photographs and other cartographic materials of the middle of the 20th century. Results. The use of photographs and satellite images, measurements of linear dimensions and calculations made it possible to establish the most accurate dimensional characteristics of the fortresses. The main conclusion of the research is the established fact that the plan of 1769–1770 of the fortresses of Grachevskaya and Mechetnaya, drawn by P.B. Inokhodtsev, is distinguished by quite a high degree of graphic correspondence with the ruined remains of these fortifications, fixed on the aerial photography of 1942–1943 and other materials from the 1960s and 1970s.